Entrepreneurial leadership models in the 21st century for vocational education - ARIFIN, M.; GUNAWAN, G. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study is a literature review that aims at describing appropriate entrepreneurial leadership models for vocational school students. There were three steps conducted in this study namely, designing the review, conducting the review, and analysis. The data of the study were taken from books and scientific articles from national and international journals. Specifically, this article describes leadership models, problems of the current leadership models, entrepreneurial leadership model, characteristics of entrepreneurial leaders, and the theoretical and practical implications of the entrepreneurial leadership model. It is expected that this article can give sufficient knowledge and information about the entrepreneurial leadership model.RESUMEN Este estudio es una revisión de la literatura que tiene como objetivo describir los modelos de liderazgo empresarial adecuados para estudiantes de escuelas vocacionales. Se realizaron tres pasos en este estudio, a saber, diseño de la revisión, realización de la revisión y análisis. Los datos del estudio fueron tomados de libros y artículos científicos. Específicamente, este artículo describe modelos de liderazgo, problemas de los modelos de liderazgo actuales, modelo de liderazgo emprendedor, características de los líderes emprendedores y las implicaciones teóricas y prácticas del modelo de liderazgo emprendedor. Se espera que este artículo pueda brindar suficiente conocimiento e información sobre el modelo de liderazgo empresarial.